Формування колекцій лікарських рослин - Porada, A.A.; Shevchenko, T.L. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
Scientifically motivated system shaping the genetic variety of the medicinal plants are designed and scheme accomodation type to exposures "Medicinal plants" by contents of acting matter is presented.